Pain assessment in intensive care units of a low-middle income country: impact of the basic educational course - Ali Sarfraz Siddiqui; Aliya Ahmed; Azhar Rehman; Gauhar Afshan (BMC Medical Education, 2023)
Abstract Background Patients admitted to ICU usually have moderate-to-severe pain at rest and during care-related activities. The “Critical Care Pain Observation Tool (CPOT)” is a reliable and validated objective assessment tool for those patients who cannot self-report pain in ICU. The objectives of the educational course were to assess the baseline knowledge, and practice of pain assessment in critically ill patients and reassess the same in all participants of the course by comparing the results of pre and post-test. Methods The educational course of six hours of contact time on the use of CPOT for pain assessment in ICU patients was designed and conducted by the authors after approval from the Ethics Review Committee, Aga Khan University. This educational course was delivered at five different tertiary care hospitals in the Sindh province of Pakistan. A pre-test consisting of 25 true/false multiple-choice questions was conducted at the beginning of the course to assess the baseline knowledge, and practice of participants regarding pain assessment in critically ill patients and the same test was taken at the end of the course. Results A total of 205 critical care physicians and nursing staff attended the courses. Both pre-test and post-test were completed by 149 (72.6%) participants, of which 53 (35.6%) were female and 96 (64.4%) were male. The mean pre-test score of participants was 57.83 ± 11.86 and the mean post-test score of participants was 67.43 ± 12.96 and this was statistically significant (p = < 0.01). In univariate analysis, the effect of training was significantly higher in the female gender (p = 0.0005) and in those participants, who belong to the metropolitan city (p = 0.010). In multivariate analysis, participants from non-metropolitan cities showed less improvement in post-test scores compared to those who come from the metropolitan city (p = 0.038). Conclusions The participating physicians and nurses showed a positive impact on the knowledge and clinical skills regarding pain assessment in CIPs. The participants from hospitals in metropolitan cities showed a significant improvement over those who were from non-metropolitan cities.